The Foreign Investment Risks of Chinese B Share Market - JIANG, MINCHANG (2014)
The objective of this dissertation is to investigate and analyse the risks existing in Chinese B share market for foreign investment. Based on the brief history of B share market as well as background information such as characteristics of Chinese stock exchange, several areas of risks are identified as: macroeconomic risks, stock volatility and return including cross-impacts among market segmentations and different countries’ markets, financial market and currency risks, and finally the political risks. According to the recent quantitative data and descriptive resources applied in the paper, conclusion can be drawn that, B share market with weak financing capability has limited attractiveness to foreign investors, and probably come to the end.